Thermoluminescence of MgF2 crystals, irradiated by electrons and protons - Zavadovskaya E. K.; Lisitsyn V. M. Viktor Mikhailovich; Rylkin Yu. A.; Shishkin I. S. (1972, 1972)
В фонде НТБ ТПУ отсутствует